Impelementasi Konsep Maksim dalam Menilai Kejujuran Komunikasi Antara Dosen dan Mahasiswa - Muttaqin, Zainul; Wijaya, Herman; Taufiq, Muh. (Universitas Hamzanwadi, 2018)
This research uses quantitative and qualitative descriptive methods. The objectives of the research are (a) to know what maxims are violated by students and lecturers of Hamzanwadi University in communicating, (b) explain the implementation of Maksim concept in assessing the honesty of Lecturer and Student ommunication at Hamzanwadi University. The location of the research was conducted on the campus of Hamzanwadi University with the sample of research were 30 students and 3 lecturers. Data collection is done by using questionnaire, observation, and documentation. Data analysis techniques used in this study are descriptive statistics in the form of frequency distribution. The value of honesty data (beginning and end) is analyzed using T-Test type Paired Samples Test, while the data of honesty value using T-Test for each Independent Samples Test. Based on the research results found that the maxim is often violated by lecturers and students PGSD in the verbal stage of the maxim quality and maxim way. Based on the normality test the level of honesty of PGSD Student communication with 0.56 rerate categorized